MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PERHOTELAN MELALUI PENERAPAN METODE DEMONSTRASI PADA SISWA KELAS XI PERHOTELAN 2 SMK NEGERI 1 TASIKMALAYA - Kalsum, Rani Novia (Jurnal Inovasi dan Teknologi Pendidikan, 2022)
The problem of this research is: a) How does the demonstration method influence Hospitality learning motivation? b) How will Hospitality learning outcomes improve by implementing the demonstration method? The aims of this research are: a) Want to know the effect of motivation to learn Hospitality after applying the demonstration method, b) Want to know the increase in Hospitality learning outcomes after implementing the demonstration method. This type of research is action research in three rounds. Each round consists of four stages, namely: design, activities and observations, reflection, and revision. The target of this research is students of Class XI Hospitality 2 of SMK Negeri 1 Tasikmalaya. The data obtained is in the form of formative test results, observation sheets of teaching and learning activities. From the analysis results, it was found that student learning outcomes increased from cycle I to cycle III, namely, cycle I (72%), cycle II (83%), cycle III (89%). The conclusion of this research is that the demonstration method has a positive effect on the motivation and learning outcomes of class